Protocol Paper: Oral Poliovirus Vaccine Transmissibility in Communities After Cessation of Routine Oral Poliovirus Vaccine Immunization. (30th October 2018) - Sarnquist, Clea; Holubar, Marisa; García-García, Lourdes; Ferreyra-Reyes, Leticia; Delgado-Sánchez, Guadalupe; Cruz-Hervert, Luis Pablo; Montero-Campos, Rogelio; Altamirano, Jonathan; Purington, Natasha; Boyle, Shanda; Modlin, John; Ferreira-Guerrero, Elizabeth; et al.
Abstract: Background: We aimed to elucidate household and community-level shedding and transmission of trivalent oral polio vaccine (tOPV) in communities with inactivated polio vaccine (IPV) routine immunization after tOPV is administered during a national health week (NHW). Methods: We conducted a 3-arm, randomized trial with data collected at baseline through 10 weeks post-NHW in households with at least 1 child <5 years old in 3 semi-rural communities in Orizaba, Mexico. Selected communities were geographically isolated but socio-demographically similar. Each community was assigned an oral polio vaccine (OPV) immunization rate: 10, 30, or 70% of participating households. From 2653 households in the 3 communities, 150 households per community were selected, for 466 in total. Households were randomized as vaccinated or unvaccinated, with only 1 child under 5 in the vaccinated household receiving OPV during the February 2015 NHW. No other community members received OPV during this NHW. Stool samples were collected up to 10 weeks post-vaccination for all members of the 466 study households and were analyzed for the presence of OPV serotypes using a multiplex polymerase chain reaction assay. Results: We will report on the factors associated with, and incidence and duration of, household and community shedding and transmission of OPV. The secondary outcomes will characterize temporal and geospatial OPV serotype shedding patterns. Conclusions: The current global polio eradication plan relies on transitioning away from OPV to IPV. This study contributes to understanding patterns of OPV shedding and transmission dynamics in communities with primary IPV immunity, in order to optimize the reduction of OPV transmission.